The antibacterial and angiogenic effect of magnesium oxide in a hydroxyapatite bone substitute - Coelho, Catarina C. (2021)
Bone graft infections are serious complications in orthopaedics and the growing resistance to antibiotics is increasing the need for antibacterial strategies. The use of magnesium oxide (MgO) is an interesting alternative since it possesses broad-spectrum antibacterial activity. Additionally, magnesium ions also play a role in bone regeneration, which makes MgO more appealing than other metal oxides. Therefore, a bone substitute composed of hydroxyapatite and MgO (HAp/MgO) spherical granules was developed using different sintering heat-treatment cycles to optimize its features. Depending on the sintering temperature, HAp/MgO spherical granules exhibited distinct surface topographies, mechanical strength and degradation profiles, that influenced the in vitro antibacterial activity and cytocompatibility. A proper balance between antibacterial activity and cytocompatibility was achieved with HAp/MgO spherical granules sintered at 1100 ºC. The presence of MgO in these granules was able to significantly reduce bacterial proliferation and simultaneously provide a suitable environment for osteoblasts growth. The angiogenic and inflammation potentials were also assessed using the in vivo chicken embryo chorioallantoic membrane (CAM) model and the spherical granules containing MgO stimulated angiogenesis without increasing inflammation. The outcomes of this study evidence a dual effect of MgO for bone regenerative applications making this material a promising antibacterial bone substitute.